Systemic functional linguistics of political articles in eastern and western online news - Abdulameer, Ali Hussein; Mohd Noor, Siti Noor Fazelah; Nasser, Wisam Khalis (HSSR, 2019)
Political discourse causes a large attendance, due to their influence on economic, cultural and societal. The current study investigates 80 political articles in Eastern and Western online news by applied transitivity analysis under the systemic functional study by (Halliday and Matthiessen, 2014).